The Tlingit Indians in Russian America, 1741-1867 - Grinëv, A. V. (Andreĭ Valʹterovich) (University of Nebraska Press, 2005)
The Tlingits, the largest Indian group in Alaska, have lived in Alaska's coastal southwestern region for centuries and first met non-Natives in 1741 during an encounter with the crew of the Russian explorer Alexei Chirikov. The volatile and complex connections between the Tlingits and their Russian neighbors, as well as British and American voyagers and traders, are the subject of this classic work, first published in Russian and now revised and updated for this English-language edition. Andrei Val'terovich Grinev bases his account on hundreds of documents from archives in Russia and the United States; he also relies on official reports, the notes of travelers, the investigations of historians and ethnographers, museum collections, atlases, illustrations, and photographs.